Avocado Rootstock Propagation Techniques to Support The Readiness of Ngesrepbalong Village, Limbangan Kendal as An Avocado Center - Retnoningsih, Amin; Rahayu, Enni Suwarsi; Mustofa , Moh. Solehatul; Akbar, Bintang Faisal; Karmesti, Danissa Wirna (Indonesian Journal of Devotion and Empowerment, 2025)
Ngesrepbalong Village in Limbangan District, Kendal, is known to be prone to landslides. Landslide mitigation through planting deep-rooted trees. This village was classified as a developing village until the end of 2023. Efforts to realize Ngesrepbalong as an avocado center required intensifying superior avocado cultivation, which involved mass availability of seeds. The problem was that the rootstock in avocado grafting was limited because one avocado only produced one seed. The production problems of the target partners of "Gunung Berkah" were overcome through socialization, training, implementation, assistance, monitoring and evaluation, and ensuring its sustainability by splitting avocado seeds/embryos into at least 2 or more. The community service activities showed that 100% of seed splitting results succeeded in growing into standard rootstock, which then became 150 superior avocado seedlings through grafting. The difference in rootstock was only in its height. For the efficiency of rootstock propagation for the Gunung Berkah group in the future, it is recommended that seed/embryo splitting be combined with the treatment of cutting the bottom of the avocado seed, giving growth hormones, and using the right planting media. The availability of avocado rootstock accelerated the availability of seeds for the intensification of superior avocado cultivation towards the realization of Ngesrepbalong as a superior avocado center.